PENGARUH PEMBELAJARAN KONTEKSTUAL DENGAN TEKNIK HANDS ON MATHEMATICS TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIK SISWA KELAS IX MTS DARUSSALAM KABUPATEN PESISIR SELATAN - Gusteti, Meria Ultra; Sefrinal, Sefrinal; Syafti, Okviani (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2018)
This research began from issues of the low Mathematic abilities students of class IX MTs Darussalam. This research is aimed to reveal the effect of Cooperatif modelswith Hands On Mathematic in mathematic students ability started from high, averageand lowof students in influencing early understanding concept ability. This research is a quasi experimental design. The population in this research is all students of class IX MTsN Darussalam Selasa. The sampling technique used is Random Sampling. Samples of this research are the students of class IX.1 as the experimental class and class IX.3 as the control class. The instrument used is a test consists of beginning capabilities test and posttest to see the communication mathematic ability. Data analysis was performed using t-test.There are some conclusions that can be acquired based on the results of research and discussion. First, the students which use contextual learning type with hands on mathematics technic have higher communication mathematic ability than students that use the conventional learning. Second, the high,average and low starting students ability which use contextual learning type with hands on mathematics technic have higher communication mathematic ability than students that use the conventional learning